In Situ Trace Elements in Quartz and K-Feldspar from Felsic Igneous Rocks: A Titanium-in-K-Feldspar Geothermometer for Natural Magmatic Systems. (1st November 2022) - Zhang, Yongmei; Gu, Xuexiang; Rusk, Brian; Mao, Wei; Wang, Jialin; Zheng, Shaohua
Abstract: Scanning electron microscope, cathodoluminescence (CL) imaging and laser ablation–inductively coupled plasma–mass spectrometry analyses were conducted on coexisting pairs of quartz and K-feldspar from 14 samples of various types of felsic igneous rocks. Difference of the concentration of trace elements in quartz and K-feldspar among plutonic, pegmatitic and volcanic rocks is closely related to the rock-forming process and P–T condition. In general, a decreasing Ti concentration and increasing Al, Li, and Ge concentrations from plutonic to pegmatitic quartz suggest a higher degree of magmatic fractionation and lower crystallization temperature. Sensitive elements to magma differentiation in K-feldspar such as Ba, Sr, and LREE show a decreasing trend from various granitic rocks to pegmatite, while Rb, Cs, Li, Ge, and P exhibit increasing trends. The K-feldspar from various types of felsic igneous rocks typically shows similar CL textures but relatively higher luminescence intensity compared with coexisting quartz. Both quartz and K-feldspar phenocrysts in the volcanic rhyolite have a bright rim and a dark core in CL images, corresponding to bimodal Ti concentrations. Among all samples, Ti concentrations in both quartz and coexisting K-feldspar positively correlate with their CL intensities, suggesting the activation of Ti-impurity in these minerals leads to increased CL intensity. Meanwhile, there is a good positive correlation between Ti concentrations in quartz and those in K-feldspar with an R 2 value of 0.86. It is considered that Ti concentrations in the both minerals are mainly temperature dependent at relatively constant pressure on basis of a fair a TiO2 restriction. Here, for the first time, we calculated a titanium-in-K-feldspar (TitaniKfs) thermometer in the form of log ( X Ti, kfs / a TiO2 ) = −(3430 ± 268)/ T (K) + (5.081 ± 0.298) for natural felsic magma systems. The Ti contents of K-feldspar (in ppm by weight) increase exponentially with reciprocal T at temperatures ranging from 500°C to 800°C, at 200–300 MPa. An application of this thermometer to granitic rocks from Xinjiang and Inner Mongolia in China fits well with other geothermometers. In addition, the present TitaniKfs thermometer is expected to be particularly useful in determining the temperature condition of K-feldspar-bearing extraterrestrial materials such as lunar rocks.